Casein kinase 2 dependent phosphorylation of neprilysin regulates receptor tyrosine kinase signaling to Akt. - Martin Siepmann; Sathish Kumar; Günter Mayer; Jochen Walter (PLoS ONE, 2010)
Neprilysin (NEP) is a type II membrane metalloproteinase that cleaves physiologically active peptides at the cell surface thus regulating the local concentration of these peptides available for receptor binding and signal transduction. In addition, the cytoplasmic N-terminal domain of NEP interacts with the phosphatase and tensin homologue deleted on chromosome 10 (PTEN) thereby regulating intracellular signaling via Akt. Thus, NEP serves dual functions in extracellular and intracellular signal transduction. Here, we show that NEP undergoes phosphorylation at serine residue 6 within the N-terminal cytoplasmic domain. In vitro and cell culture experiments demonstrate that Ser 6 is efficiently phosphorylated by protein kinase CK2. The phosphorylation of the cytoplasmic domain of NEP inhibits its interaction with PTEN. Interestingly, expression of a pseudophosphorylated NEP variant (Ser6Asp) abrogates the inhibitory effect of NEP on insulin/insulin-like growth factor-1 (IGF-1) stimulated activation of Akt. Thus, our data demonstrate a regulatory role of CK2 in the interaction of NEP with PTEN and insulin/IGF-1 signaling.